Techincal-financial analysis of a grid-connected photovoltaic power system in the Amazon Region - Costa, Tatiane Silva; Santos, Manoel Roberval Pimentel (Revista Hipótese, 2018)
In 2012, the approval of Normative Resolution n° 482, began to regulate the Brazilian consumer allowing to generate the own electric energy from of renewable sources. In this context, a project was prepared for the implementation in the municipality of Santarém, Pará, in a middle-class residence whose average monthly consumption is around 440 kWh / month, with all calculations made, it was concluded the technical and legal feasibility of the system in accordance with what is allowed in Brazilian legislation.